Imaging glucose metabolism, neuroinflammation, and cannabinoid receptor 1 in transgenic mouse models of Alzheimer’s disease - Takkinen, Jatta (fi=Turun yliopisto|en=University of Turku|, 2019)
The pathophysiological cascade leading to Alzheimer’s disease is characterized by the accumulation of destructive β-amyloid in the brain. Convincing evidence has also shown that cerebral energy hypometabolism and an overproduction of translocator protein during neuroinflammation, as well as deficits in the endocannabinoid system, play major roles in progression of the disease. Monitoring temporal changes inside the diseased brain with noninvasive positron emission tomography (PET) would be a unique translational tool, bridging the gap between disease models and patients and aiding in the discovery of disease-modifying therapies against Alzheimer’s disease. The aim of this thesis was to evaluate the translational feasibility of cerebral glucose metabolism targeting PET tracer 18F-FDG in APPswe-PSIdE9, Tg2576, and APP/PS1-21 mouse models of Alzheimer’s disease. In addition, this thesis aimed to examine the suitability of neuroinflammation-specific protein targeting tracer 18F-DPA-714 for longitudinal follow-up in aging APP/PS1-21 mice and whether it correlates with changes in glucose metabolism. Furthermore, the translational applicability of 18F-FMPEP-d2 was evaluated as a tool to assist in preclinical research targeting cannabinoid receptor 1 (CB1R) in wild-type and APP/PS1-21 mice. Of the tested models, APP/PS1-21 mice demonstrated the most aggressive β-amyloid pathology. Furthermore, repeated PET scans with 18F-FDG and 18F-DPA-714 detected progressive glucose hypometabolism and neuroinflammation in the APP/PS1-21 model as the mice aged. However in the APPswe-PSIdE9 and Tg2576 mouse models, only a weak or non-altered glucose metabolism was observed. 18F-FMPEP-d2 was able to reveal altered CB1R availability when aging APP/PS1- 21 mice were followed with repeated PET scans. This thesis work demonstrated that Alzheimer’s disease mouse models differ in terms of amyloidosis and cerebral glucose metabolism, which creates challenges when comparing the research results between the models. The feasibility of 18F-FDG small animal PET depends on the chosen disease model and environmental factors. In the APP/PS1-21 model, longitudinal 18FFMPEP- d2 and 18F-DPA-714 PET scans were able to demonstrate pathological features related to Alzheimer´s disease, which were confirmed by ex vivo examinations.

Aivojen energia-aineenvaihdunnan, tulehduksen ja tyypin 1 kannabinoidireseptorin kuvantaminen Alzheimerin taudin muuntogeenisissä hiirimalleissa Alzheimerin taudin keskeisimmät aivomuutokset ovat sakkautuvien β-amyloidipeptidien muodostuminen plakeiksi, aivojen heikentynyt energia-aineenvaihdunta, tulehduksen lisääntyminen ja endokannabinoidijärjestelmässä tapahtuvat muutokset, jotka lopulta johtavat hermosolujen vaurioitumiseen ja tyypillisten kognitiivisten häiriöiden ilmentymiseen. Aivomuutoksia on mahdollista seurata elävässä tutkittavassa kajoamattoman positroniemissiotomografia (PET)-kuvantamisen avulla. Muuntogeenisten Alzheimerin taudin eläinmallien PET-kuvantaminen antaa ainutlaatuisen mahdollisuuden selvittää sairauden monimutkaisia patologisia tapahtumia ja seurata uusien lääkeaineiden vaikutusta ja turvallisuutta. Tämän tutkimuksen tavoitteena oli arvioida aivojen glukoosiaineenvaihduntaa mallintavan 18FFDG-merkkiaineen soveltuvuutta muuntogeenisten APPswe-PSIdE9, Tg2576 ja APP/PS1-21 hiirimallien pieneläinPET-kuvantamiseen. Toisena tavoitteena oli arvioida tulehdusproteiiniin sitoutuvan PET-merkkiaineen, 18F-DPA-714, soveltuvuutta aivoissa etenevän tulehduksen seuraamiseen muuntogeenisessä APP/PS1-21 hiirimallissa. Kolmantena tavoitteena oli tutkia tyypin 1 kannabinoidireseptori-PET-merkkiaineen, 18F-FMPEP-d2, soveltuvuutta pieneläinkuvantamiseen villityypin hiirillä ja Alzheimerin taudin reseptorimuutosten seuraamiseen APP/PS1-21 hiirimallilla. APP/PS1-21 hiirimallin β-amyloidipatologia eteni muita malleja nopeammin. Lisäksi hiirimallin aivojen glukoosiaineenvaihduntaa mallintavan merkkiaineen kertymä heikentyi ja tulehdusproteiiniin sitoutuvan merkkiaineen määrä kasvoi, kun hiiriä kuvattiin toistuvasti PETmenetelmällä. Vastaavasti APPswe-PSIdE9 ja Tg2576 hiirimalleilla havaittiin vain lievää tai olematonta glukoosiaineenvaihdunnan heikkenemistä. 18F-FMPEP-d2 PET-tutkimukset osoittivat alentunutta merkkiainekertymää APP/PS1-21 hiirimallissa verrattuna terveisiin eläimiin, ja soveltuvuutta tuleviin pieneläinkuvantamistutkimuksiin. Tutkimustulokset osoittivat, että muuntogeeniset eläinmallit eroavat merkittävästi toisistaan, mikä asettaa haasteita tutkimustulosten vertaamiseen mallien kesken. Aivojen 18F-FDG-kertymä vaihtelee tautimallin ja ympäristötekijöiden mukaan, mikä tuo rajoitteita pieneläinkuvantamisen toteuttamiseen. Sekä 18F-DPA-714- ja 18F-FMPEP-d2-merkkiaineet pystyivät osoittamaan Alzheimerin taudille tyypillisiä aivomuutoksia APP/PS1-21 hiirissä, mitkä voitiin varmentaa ex vivo menetelmin hiirten aivoleikkeistä.